Genetic Relatedness of Lentil (Lens Culinaris L.) Germplasm by using SSR Markers - Kushwaha, U. K. S.; Ghimire, S. K.; Yadav, N. K.; Ojha, B. R. (International Journal of Applied Sciences and Biotechnology, 2013)
Ninety six lentil accessions from different origins were collected from National Grain Legume Research Program, Rampur; Regional Agriculture Research Station, Nepalgunj and National Agriculture Genetic Resource Center, Khumaltar, Lalitpur. Among them; four lines were Nepal Local, forty two lines were Nepal Cross; forty seven lines were ICARDA Line and finally three lines were Indian Line. All ninety six accessions were analysed by DNA fingerprinting using thirty three selected polymorphic SSR markers. The characterization was performed in Biotechnology Unit, Nepal Agricultural Research Council, Khumaltar, Lalitpur by using standard protocols. Molecular variance analysis showed that 14 % genetic variation was found between population and 86 % genetic variation was found within population with estimated variance 0.23 between population and 1.35 within population. Highest genetic distance (9) was found between landrace ILL-7979 and RL-20. In the same way, highest Nei genetic distance (0.03) between population was shown by population 1 and population 4; and lowest genetic distance were observed within the same population accessions. The heterozygosity was probably due to the introgression of genes or duplication of microsatellite motif during the breeding and or the course of lentil line evolution. All the accessions included in this study displayed significant amount of genetic variability and genetic relatedness due to different center of origin and different genetic constitutions. The diversity detected in this study may constitute the new materials for future systematic lentil breeding programs. DOI: http://dx.doi.org/10.3126/ijasbt.v1i3.8608 Int J Appl Sci Biotechnol, Vol. 1(3) 2013 : 132-136